Characteristics and Changes over Time of Alcohol-Related Chronic Liver Diseases in Italy - Tommaso Stroffolini; Evangelista Sagnelli; Caterina Sagnelli; Filomena Morisco; Sergio Babudieri; Caterina Furlan; Mario Pirisi; Maurizio Russello; Antonina Smedile; Mariantonietta Pisaturo; Piero Luigi Almasio (Canadian Journal of Gastroenterology and Hepatology, 2018)
Introduction. To evaluate the characteristics of alcohol-related chronic liver disease (CLD) in Italy and their potential changes over time. Patients and Methods. Subjects with CLD were enrolled in two national surveys performed in 2001 and in 2014 in Italy. The two surveys prospectively recruited patients aged ≥ 18 years referring to more than 80 Italian liver units scattered all over the country using similar clinical approach, analytical methods, and threshold of risky alcohol intake definition (≥ 3 units/day in men and ≥ 2 units/day in women). Results. Out of 12,256 enrolled subjects, 2,717 (22.2%) reported a risky alcohol intake. Of them, anti-HCV positive was observed in 48.3% of subjects. The overall sex ratio (M/F) was 3.1, decreasing from 3.8 in 2001 to 1.3 in 2014. Women were significantly older than men (58.9 versus 53.1 years; p<0.01) and an increasing ageing over time was observed in both sexes. The proportion of subjects with liver cirrhosis increased over time in both sexes, and decompensated stage (Child B or C) was detected in 55.9% of cases in 2001 and 46.0% in 2014. Conclusions. Risky alcohol intake plays a role in more than one-fifth of CLD in Italy, with a shift over time towards an older age and a more severe liver disease stage. These data put alcohol back in the spotlight with an important role in CLD in the years to come in Italy.